Preparation, Electronic Structure and Optical Properties of the Electrochromic Thin Films - Lukaszewicz, T.; Ravinski, A.; Makoed, I. (Nonlinear Analysis: Modelling and Control, 2004)
A new multilayer electrochromic device has been constructed according to the following pattern: glass1/ITO/WO3/gel electrolyte/BP/ITO/glass2, where ITO is a transparent conducting film made of indium and tin oxide and with the surface resistance equal 8–10 Ω/cm2 . The electrochromic devices obtained in the research are characterized by great (considerable) transmittance variation between coloration and bleaching state (25–40% at applied voltage of 1.5 to 3 V), and also high coloration efficiency (above 100 cm2 /C). Selfconsistent energy bands, dielectric permittivity and optical parameters are calculated using a full-potential linear muffin-tin orbital method. The numerical solution of the Debye-Smoluchowski equations is developed for simulating recombination probability of Li+ ions in amorphous electrolyte.